VALIDATION OF A METHODOLOGY FOR INPATIENT PHARMACOTHERAPY FOLLOW-UP - BECERA C. M.Sc., Jesus; MARTÍNEZ M. Ph.D., Fernando; BOHORQUEZ C. M.Sc., Martha; GUEVARA U. Q.F., Martha L.; RAMÍREZ N. Q.F., Edgar (Vitae, 2013)
Background: Pharmacotherapy follow-up is a practice in which the pharmacist assumes responsibility for the patient’s drug-related Problems. Its goal is to achieve positive clinical outcomes. Methods to perform pharmacotherapy follow-up have centered principally on ambulatory patients. Objective: The purpose of this study is to propose and validate a methodology for inpatient pharmacotherapy follow-up. Methods: A systematic review was performed. This consisted in a comprehensive search of databases containing studies published in English or Spanish during 1998 - 2008, and that sought to improve the transfer of accurate information about Pharmacotherapy follow-up in inpatients. The key terms used to conduct the search were identified in consultation with clinical experts and included: Pharmacotherapy follow-up methods, pharmacotherapy follow-up, drug therapy problems, and validation. A comparative table was elaborated to differentiate and evaluate the advantages of each of the proposed methodologies. The information gathered allowed to propose a sequence of general steps for inpatient Pharmacotherapy follow-up. To validate the methodology, a descriptive study was carried out with 32 randomly selected patients and was independently followed up by two pharmacists to assess the reproducibility of the process. Results: Pharmaceutical Care Practice: The Clinician’s Guide, proposed by Cipolle & Strand. Applied Therapeutics: The Clinical Use of Drugs, the DÁDER method, and the IASER program, were selected. 79 drug therapy problems (DTPs) were identified and resolved, where errors in necessity of medication had the highest incidence (46.6%), followed by effectiveness (24.5%) and safety (28.9%). The degree of agreement among researchers in the identification and resolution of DTPs was quantified using the kappa coefficient, showing a high concordance (90% CI). The Fisher’s exact test determined that DTPs are related to the duration of the follow up, number of medications, length of the stay and previous hospitalizations. Conclusions: The methodology allows identifying, preventing and resolving DTPs. It proved to be reproducible and have a high degree of concordance between applications.